"Bind him hand and foot, and throw him into…" Dependence of Matt 22:13 on Plato’s Euthyphro 4c? - Kozłowski, Jan (Verbum Vitae, 2024)
There is a striking similarity, both in form and content, between Matt 22:13, where the king punishes the invited guest for lacking a “wedding robe,” and Plato’s Euthyphro 4c, where Euthyphro’s father punishes the hired laborer for murder. The most probable explanation for these similarities is that Matt 22:13 reflects an echo of Plato’s text.